EASI Transformation: An Efficient Transient Expression Method for Analyzing Gene Function in Catharanthus roseus Seedlings - Mortensen, Samuel; Bernal-Franco, Diana; Cole, Lauren F.; Sathitloetsakun, Suphinya; Cram, Erin J.; Lee-Parsons, Carolyn W. T. (Frontiers in Plant Science, 2019)
The Catharanthus roseus plant is the exclusive source of the valuable anticancer terpenoid indole alkaloids, vinblastine (VB) and vincristine (VC). The recent availability of transcriptome and genome resources for C. roseus necessitates a fast and reliable method for studying gene function. In this study, we developed an Agrobacterium-mediated transient expression method to enable the functional study of genes rapidly in planta, conserving the compartmentalization observed in the VB and VC pathway. We focused on 1) improving the transformation method (syringe versus vacuum agroinfiltration) and cultivation conditions (seedling age, Agrobacterium density, and time point of maximum transgene expression), 2) improving transformation efficiency through the constitutive expression of the virulence genes and suppressing RNA silencing mechanisms, and 3) improving the vector design by incorporating introns, quantitative and qualitative reporter genes (luciferase and GUS genes), and accounting for transformation heterogeneity across the tissue using an internal control. Of all the parameters tested, vacuum infiltration of young seedlings (10-day-old, harvested 3 days post infection) resulted in the strongest increase in transgene expression, at 18 - 57 fold higher than either vacuum or syringe infiltration of other seedling ages. Endowing the A. tumefaciens strain with the mutated VirGN54D or silencing suppressors within the same plasmid as the reporter gene further increased expression by 2 – 10 fold. For accurate measurement of promoter transactivation or activity, we included an internal control to normalize the differences in plant mass and transformation efficiency. Including the normalization gene (Renilla luciferase) on the same plasmid as the reporter gene (firefly luciferase) consistently yielded a high signal and a high correlation between RLUC and FLUC. As proof of principle, we applied this approach to investigate the regulation of the CrSTR1 promoter with the well-known activator ORCA3 and repressor ZCT1. Our method demonstrated the quantitative assessment of both the activation and repression of promoter activity in C. roseus. Our efficient Agrobacterium-mediated seedling infiltration (EASI) protocol allows highly efficient, reproducible, and homogenous transformation of C. roseus cotyledons and provides a timely tool for the community to rapidly assess the function of genes in planta, particularly for investigating how transcription factors regulate alkaloid biosynthesis.